Using S2P for routing awareness in tuple-based pervasive systems. (22nd July 2009) - Rahmani, Shahpour; Sharifi, Mohsen; Kolahdooz, Saman
Existing tuple-based middleware-level mechanisms often use broadcasting for resource discovery in pervasive systems. We present a new routing-aware mechanism based on S2P networks. Each peer has a routing table containing information on the peers that most recently have provided this peer' requested resources. Each peer caches and uses such information to route its requests peer to peer. We implemented our routing mechanism in Java and ran it on a prototyped system under LIME in a MANET. The results demonstrated approximately 53% improvement in the query processing response time of the constructed pervasive system compared to the response time of the same system running a default routing mechanism in LIME.